Candida albicans SR-Like Protein Kinases Regulate Different Cellular Processes: Sky1 Is Involved in Control of Ion Homeostasis, While Sky2 Is Important for Dipeptide Utilization - Brandt, Philipp; Gerwien, Franziska; Wagner, Lysett; Krüger, Thomas; Ramírez-Zavala, Bernardo; Mirhakkak, Mohammad H.; Schäuble, Sascha; Kniemeyer, Olaf; Panagiotou, Gianni; Brakhage, Axel A.; Morschhäuser, Joachim; Vylkova, Slavena (Frontiers in Cellular and Infection Microbiology, 2022)
Protein kinases play a crucial role in regulating cellular processes such as growth, proliferation, environmental adaptation and stress responses. Serine-arginine (SR) protein kinases are highly conserved in eukaryotes and regulate fundamental processes such as constitutive and alternative splicing, mRNA processing and ion homeostasis. The Candida albicans genome encodes two (Sky1, Sky2) and the Candida glabrata genome has one homolog (Sky1) of the human SR protein kinase 1, but their functions have not yet been investigated. We used deletion strains of the corresponding genes in both fungi to study their cellular functions. C. glabrata and C. albicans strains lacking SKY1 exhibited higher resistance to osmotic stress and toxic polyamine concentrations, similar to their ortholog Sky1 in Saccharomyces cerevisiae. Deletion of SKY2 in C. albicans resulted in impaired utilization of various dipeptides as the sole nitrogen source. Subsequent phosphoproteomic analysis identified the di- and tripeptide transporter Ptr22 as a potential Sky2 substrate. Sky2 seems to be involved in Ptr22 regulation since overexpression of PTR22 in the sky2∆ mutant restored the ability to grow on dipeptides and made the cells more susceptible to the dipeptide antifungals Polyoxin D and Nikkomycin Z. Altogether, our results demonstrate that C. albicans and C. glabrata Sky1 protein kinases are functionally similar to Sky1 in S. cerevisiae, whereas C. albicans Sky2, a unique kinase of the CTG clade, likely regulates dipeptide uptake via Ptr22.